Letter to Editor on "Efficacy of Active Exercises to Improve Range of Motion in Knee Joint After Total Knee Arthroplasty. A Randomized Controlled Trial"...Mogensen L, Rasmussen T, Rasmussen J, et al. Physiotherapy Research International. 2026;31(3):1-10. - Bano, Azmat; Aggarwal, Amita (Physiotherapy Research International, 2026)
This article critically examines the methodology and statistical analysis of a randomized controlled trial investigating the efficacy of active exercises to improve knee joint range of motion (ROM) after total knee arthroplasty (TKA). Key concerns include the use of cluster randomization without accounting for intra-cluster correlation, short intervention duration with no long-term follow-up, reliance on self-reported adherence, lack of preoperative ROM data, and inappropriate statistical tests that may underestimate errors and bias results. The critique also highlights issues with treatment dose adherence, absence of standardized exercise force, and potential attrition and Type 1 errors due to analysis choices. These observations aim to inform future research design and interpretation in TKA rehabilitation studies.